Advancements in spontaneous microbial desalination technology for sustainable water purification and simultaneous power generation: A review. (1st November 2021) - Patel, Monika; Patel, Shiv Singh; Kumar, Pradip; Mondal, Dehi Pada; Singh, Bhupendra; Khan, Mohd Akram; Singh, Shiv
Abstract: Population growth and rapid urbanization have put a lot of pressure on the already scarce freshwater around the globe. The availability of freshwater is not only limited but it is non-uniform also. Available desalination technologies help mitigate water shortage; however, these techniques are energy-intensive and unsustainable. Desalination technologies utilizing renewable energy and bio-electrochemical systems have been developed to achieve limited sustainability. With technological advancements, microbial desalination cell (MDC) has been developed which is capable of desalination, wastewater treatment, and power generation simultaneously. This review critically examined the performance of various MDC techniques concerning their stimulus parameters including COD removal, total desalination rate, total dissolved solids reduction rate, Coulombic efficiency, and power density. Limitations of MDCs have also been incorporated in the review. Work on MDC coupled with other robust desalination techniques offering advantages such as better desalination and more water recovery e.g. osmotic-MDC etc. has been included. Researchers have tremendously worked on MDCs with different electro-catalysts. Few of these are not sustainable and costly. Authors have reviewed critically with belief that it will pave a way for the commercialization of this eco-friendly technology. Graphical abstract: Image 1 Highlights: This review discusses how MDC works and the effect of other parameters on it. MDC performance may enhance through efficient electrocatalysts and electrolytes. Different configurations and hybrid MDCs are comparatively more efficient.